Exiled Hispanism: The Literary and Publishing World of Spanish Intellectuals who Arrived in New York (Castilla. Estudios de Literatura, 2018)
This paper aims to delve into the literary and publishing world of the Spanish intellectuals and artists exiled in New York through three axes: a brief analysis of the pre-war Hispanism that led to the reception of intellectuals during and after the Civil War; a review of the publishing situation of the war and immediate postwar period; and a further review of the most relevant Spanish magazines, publishers and bookstores ‒American, pre-war Spanish, and founded by exiled‒ of the later decades, being the exiled community already settled.
Keywords: hispanism; exile; New York; intellectuals; literatura; publishers